2008
DOI: 10.1097/brs.0b013e318186b292
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Bone Turnover on the Biomechanical Properties of the L3 Vertebra in an Ovine Model of Early Stage Osteoporosis

Abstract: These findings show that OVX resulted in changes in bone turnover, which reduced biomechanical properties in a model of early stage osteoporosis. These differences were present despite microarchitecture or BMD remaining unchanged. In the future, the ability to assess site-specific bone turnover would greatly enhance the accuracy with which fracture risk could be predicted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…In line with international literature ovariectomy alone had only minor effects on bone mass and structure . However, effects on the cortical bone reach level of significance 12 months after OVX comparable to results published recently by other groups .…”
Section: Discussionsupporting
confidence: 90%
“…In line with international literature ovariectomy alone had only minor effects on bone mass and structure . However, effects on the cortical bone reach level of significance 12 months after OVX comparable to results published recently by other groups .…”
Section: Discussionsupporting
confidence: 90%
“…Comparison between the two groups found that the modulus was less in the OVX group than in the control group at all three locations. This is consistent with previous work on these animals where we showed using a series of fluorochrome dyes, that following ovariectomy there was a significant increase in trabecular bone turnover (Kennedy et al, 2008).…”
Section: Discussionsupporting
confidence: 82%
“…We have previously demonstrated an increase compact bone turnover and porosity in an ovine model of osteoporosis during the initial 12‐months postovariectomy without adversely affecting biomechanical properties 5. Conversely, we have also demonstrated a significant reduction in the biomechanical properties of trabecular bone associated with increased turnover 9. Here we examine the effect of estrogen deficiency on compact bone geometry, intracortical remodeling, porosity, and biomechanical parameters in an ovine model of osteoporosis over a 31‐month period.…”
mentioning
confidence: 85%